Respuesta :

Answer:

5

Step-by-step explanation:

10x - 20 =10*x - 2*10 = 10*(x - 2)

2x-4  = 2*x - 2*2 = 2*(x - 2)

[tex]\dfrac{10x-20}{2x-4}=\dfrac{10*(x-2)}{2*(x-2)}=5[/tex]

Answer: x= -3

Step-by-step explanation:Simplifying 10x + 20 = 2x + -4. Reorder the terms: 20 + 10x = 2x + -4 Reorder the terms: 20 + 10x = -4 + 2x Solving 20 + 10x = -4 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 20 + 10x + -2x = -4 + 2x + -2x Combine like terms: 10x + -2x = 8x 20 + 8x = -4 + 2x + -2x Combine like terms: 2x + -2x = 0 20 + 8x = -4 + 0 20 + 8x = -4 Add '-20' to each side of the equation. 20 + -20 + 8x = -4 + -20 Combine like terms: 20 + -20 = 0 0 + 8x = -4 + -20 8x = -4 + -20 Combine like terms: -4 + -20 = -24 8x = -24 Divide each side by '8'. x = -3 Simplifying x = -3